Cohabitation and religious marriage : status, similarities and solutions / [edited by] Rajnaara Akhtar, Patrick Nash, Rebecca Probert. - Akhtar, Rajnaara; Nash, Patrick (Law teacher); Probert, Rebecca (Bristol University Press, 2020)
Cohabiting couples and those entering religious-only marriages all too often end up with inadequate legal protection when the relationship ends. Yet, despite this shared experience, the linkages and overlaps between these two groups have largely been ignored in the legal literature. Based on wide-ranging empirical studies, this timely book brings together scholars working in both areas to explore the complexities of the law, the different ways in which individuals experience and navigate the existing legal framework and the potential solutions for reform. Illuminating pressing implications for social policy, this is an invaluable resource for policy makers, practitioners, researchers and students of family law.